2020
DOI: 10.12740/app/122210
|View full text |Cite
|
Sign up to set email alerts
|

Problems with treatment of COVID-19 (+) patientwith psychiatric disorder – a case report

Abstract: The COVID-19 pandemic has put an unusual strain on medical staff across the globe. Psychiatric disorders and their effect on patients' behavior turn the management of coronavirus disease into an even more of a challenging task. In this paper we present a case report of a COVID-19-positive patient suffering from organic mental disorders and alcohol dependence syndrome, thus shedding some light on a perspective of mental health professionals working in a psychiatric hospital setting, transformed into an infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The situation is worsened by the limitations of the patient's direct contact with a doctor or psychotherapist. A special group is made up of people with diagnosed markers of the presence of the SARS-CoV-2 virus and who needed treatment for both mental and infectious disease [31]. It has been observed that the treatment of a psychiatric patient carrying the SARS-CoV-2 virus is the source of several problems, both therapeutic and organizational.…”
Section: Healthy People Living In the Pandemic Areasmentioning
confidence: 99%
“…The situation is worsened by the limitations of the patient's direct contact with a doctor or psychotherapist. A special group is made up of people with diagnosed markers of the presence of the SARS-CoV-2 virus and who needed treatment for both mental and infectious disease [31]. It has been observed that the treatment of a psychiatric patient carrying the SARS-CoV-2 virus is the source of several problems, both therapeutic and organizational.…”
Section: Healthy People Living In the Pandemic Areasmentioning
confidence: 99%